The relevance of psychological strength for physical and psychological well-being in trauma-exposed women. - Ruiz-Párraga, Gema Teresa; Serrano-Ibáñez, Elena Rocío; Gómez-Pérez, Lidia; Ramírez-Maestre, María del Carmen; Esteve-Zarazaga, Rosa; López-Martínez, Alicia Eva (Wiley, 2021)
Background: Traumatic experiences have consistently been linked to poor health and well-being, particularly in women. Psychological factors have been theorized to directly affect the reporting of physical symptoms and perceptions of general health. Posttraumatic stress disorder (PTSD) has been proposed as a major pathway through which trauma affects health and emotion dysregulation. Trauma is considered to be a key psychological variable in the pathogenesis of PTSD. Fortunately, not all women who have experienced trauma manifest adverse effects. Resilience acts as a psychological protective variable following trauma. The present study tested a hypothetical model of the contribution of resilience, emotional dysregulation, and PTSD symptoms to physical and psychological well-being in a large sample of trauma-exposed women. Method: Transversal study with 753 female participants. Structural modelling was used to test linear associations between variables. Results: After experiencing trauma, resilience was negatively and significantly associated with emotional dysregulation, which, in turn, was positively associated with PTSD symptoms. Both resilience and PTSD symptoms were associated with physical and psychological well-being. Conclusion: The results suggest that resilience and emotional dysregulation are relevant to the health and well-being of women with PTSD symptoms and may help guide the development of psychological treatment in this group. Therefore, these findings may be relevant in promoting health and well-being in such women, and may help to identify individuals who would receive the most benefit from interventions addressing emotional regulation and psychological resilience.
https://openpolicyfinder.jisc.ac.uk/id/publication/3792
Keywords: Resiliencia (Psicología); Madurez emocional; Trauma psíquico; Mujeres; Salud; Resilience; Emotional dysregulation; PTSD symptoms; Women; Health; Well-being